Regulation mechanism of microRNAs in cardiac cells-derived exosomes in cell crosstalk - Lin, Shanshan; Yang, Yuanjian; Zhou, Zhou; Li, Wen; Wang, Xianliang; Liu, Yu; Bi, Yingfei; Mao, Jingyuan (Frontiers in Pharmacology, 2024)
The heart is a multicellular system, and the intercellular crosstalk mechanism is very important for the growth and development of the heart and even the organs, tissues, and cells at a distance. As a kind of extracellular vesicle, exosomes are released by different types of cells and can carry specific genetic material, endosomal proteins, cytokines, etc., which are the main material basis for mediating cell crosstalk mechanism. Among them, microRNA carried by cardiac cells-derived exosomes have highly conserved sequences and play a key role in regulating the function of organs, tissues, and cells related to cardiovascular diseases and their complications and comorbidities, which have attracted extensive attention in the medical community in recent years. Following up on the latest research progress at home and abroad, this review systematically summarized the regulatory role of microRNA from cardiac cells-derived exosomes in various cell crosstalk, including not only cardiac cells (including cardiomyocytes, fibroblasts, myofibroblast, cardiac progenitor cells, cardiac microvascular endothelial cells, cardiosphere-derived cells, etc.) but also tumor cells, bone marrow progenitor cells, and other tissue cells, in order to provide a reference for the prevention and treatment of cardiovascular diseases and their complications and comorbidities.